Design and Characterization of a Miniature Bio-Inspired Mobile Robot - Velázquez, Ramiro; Claudia L. Garzon-Castro; Acevedo, Mario; Orvañanos-Guerrero, María T.; Amir A. Ghavifekr (My University, 2021)
This paper presents the design, implementation, and characterization of a miniature crab-like walking robot. The first prototype developed is a four-legged servomotor actuated machine that exhibits compact dimensions, low mass, and is capable of overcoming obstacles and moving on irregular terrain and confined spaces. Its bio-inspired design ensures the compliance of its locomotion mechanism even in the presence of external disturbances. The mechanical design, the implementation of the prototype, and its electronic control approach are first discussed. Next, a kinematic analysis characterizing its motion is presented. The aim of this device is to serve as an educational supporting platform for understanding robot kinematics and legged locomotion.